PENGARUH SUSTAINABILITY REPORT TERHADAP KINERJA KEUANGAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Mokhammad Fahmi Sidiq; Fika Azmi (Jurnal AKTUAL, 2022)
This study aims to obtain empirical evidence of the effect of a moderated sustainability report on good corporate governance variables on financial performance. The samples of this study were 4 commercial banks listed on the IDX that met the CGPI requirements during the period 2013-2020 so that 32 samples were obtained using purposive sampling technique. This study uses secondary data with the SEM Partial Least Square (PLS) analysis tool model. The results of this study indicate that the sustainability report of the social dimension has a positive and significant effect on banking financial performance, the sustainability report of the economic dimension and the environmental dimension has no effect on the financial performance of banks, and the sustainability report of the economic dimension, social dimension, and environmental dimension moderated by the variable of good corporate governance. does not affect the financial performance of banks.